2009
DOI: 10.1177/147323000903700224
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization and Anti-tumour Effects of Cytosine Deaminase and Thymidine Kinase Fusion Suicide Gene in Human Adenoid Cystic Carcinoma Cells

Abstract: Herpes simplex virus thymidine kinase (HSV-TK) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Single suicide gene therapy has various limitations, drug resistance being the most common. The high incidence of tumor gene mutation is the foundation of drug resistance (20). Since different types of tumor cells have differences in sensitivity to different enzyme/prodrug systems, and tumor in vivo often exists in the form of a variety of clonogenic tumor cells, making it difficult to achieve radical tumor eradication by application of a single enzyme/prodrug system.…”
Section: Discussionmentioning
confidence: 99%
“…Single suicide gene therapy has various limitations, drug resistance being the most common. The high incidence of tumor gene mutation is the foundation of drug resistance (20). Since different types of tumor cells have differences in sensitivity to different enzyme/prodrug systems, and tumor in vivo often exists in the form of a variety of clonogenic tumor cells, making it difficult to achieve radical tumor eradication by application of a single enzyme/prodrug system.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-prodrug therapy has been shown previously to enhance tumor cell sensitivity to radiation therapy (Huang et al, 2009; Robson et al, 2005). In a mouse model of human glioma, Kaliberov et al (Kaliberov et al, 2007) observed higher survival rates with a combination therapy as opposed to treatment with either cytosine deaminase/5-FC or radiation alone.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Kong et al [24] have exploited adenovirus-mediated TK/CD double suicide genes, which are more effective in killing breast cancer cells in vitro . Huang et al [25] have excised TK/CD suicide gene therapy with combination of radiotherapy to enhance radio-sensitivity of tumor. Liao et al [26] have found that radiation can enhance therapeutic efficacy of hTERTp-mediated gene therapy.…”
Section: Discussionmentioning
confidence: 99%